Health Counseling on The Importance of Personal Hygiene to Prevent Scabies In The Special Child Development Institution (LPKA) Class II in Jakarta - Rosmawaty Lubis; Andi Julia Refiana; Nirmawati (Rajaki of Tulip Medika Publisher, 2024)
Scabies is a skin disease caused by infection with an ectoparasite, namely the mite Sarcoptes scabiei var hominis, a disease related to the environment and human behavior. One of the health problems in LPKA Class II Jakarta is scabies, which is suffered by most of the students. From LPKA data it is known that there are 52 children out of 80 people (65%) in LPKA residents who suffer from scabies. Lack of personal hygiene among students such as bathing twice a day using soap, cleanliness of clothes, and towels, cleanliness of beds, and cleanliness of rooms are factors causing the high incidence of scabies in this institution. This counseling activity aims to provide information and education to the students of the pecial Child Development Institution (LPKA) Class II in Jakarta about health, especially scabies skin disease caused by the small mite Sarcoptes scabiei. Apart from that, also asked the students to get used to living a clean and healthy life in order to avoid various kinds of diseases including skin disease scabies. The activity carried out was to provide health education, especially about scabies, which affects many children living in LPKA. On this occasion, motivation is also given to adopt clean and healthy living behavior to avoid various diseases including scabies.